2016
DOI: 10.1037/neu0000271
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing card-sorting performance: Effects of working memory load and age-related changes.

Abstract: Rule inference on WCST-like card-sorting tasks appeared to be selectively impaired when the amount of information to be integrated in working memory increases or when working memory capacity is reduced (as in older individuals). Our findings indicate that measuring integration errors as an index of a distinct rule-inference process can improve the understanding and interpretability of WCST performance. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
61
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 52 publications
4
61
2
1
Order By: Relevance
“…A computerized version of the Wisconsin Card Sorting Test (Barceló 2003;Lange et al 2015Lange et al , 2016a was used. Participants were instructed to match a stimulus card to one of four key cards on each trial.…”
Section: Task and Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…A computerized version of the Wisconsin Card Sorting Test (Barceló 2003;Lange et al 2015Lange et al , 2016a was used. Participants were instructed to match a stimulus card to one of four key cards on each trial.…”
Section: Task and Proceduresmentioning
confidence: 99%
“…In addition, setloss errors were analyzed. These errors occur on trials following a positive feedback when the rule has not changed (Lange et al 2016a). Note that this definition differs from the one of Lange et al (2016b), as they counted set-loss errors exclusively on the first trial after the correct rule has been identified or the last trial before the rule changes.…”
Section: Task and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations